Numerical and experimental investigations on structural intensity in plates. (15th April 2016) - Petrone, G.; De Vendittis, M.; De Rosa, S.; Franco, F.
Abstract: The need of reducing the vibration levels is one of the most important points in many engineering fields. Therefore, the knowledge of the vibrational field can be a useful and efficient tool in problems regarding acoustic and mechanical insulation. This paper is focused on the experimental measurements and numerical predictions of the structural intensity fields in rectangular plates. The method is applied by simulating finite plates and the effects of constraints, load conditions, damping, thickness and fibres orientation are investigated. Experimental measurements are carried out on both aluminium sandwich and composite (orthotropic) panels; the results are compared through a mixed numerical/experimental approach with purely numerical predictions. The mixed approach based on both experimental and numerical information is proposed since it can give good indications of the structural intensity fields, can offer information about the energy transmission paths and can fruitfully use the numerical generated information.